Assessing flow accumulation area of Sungai Kuantan watershed using GIS techniques - Che Ku Aili Nurfateen, Che Ku Ahmad (2012)
Flooding is the most significant natural hazard in Malaysia in terms of population affected, frequency, area extent, flood duration and social economic damage. Recent years, flooding occurred in areas that have been developed. This cause a lot of cost to be borne by the government and public. The study is constructed to establish dataset consisting topography map and to analyze geographic distribution of flow accumulation at Sungai Kuantan watershed. The Geographic Information System (GIS) have been used to deal with spatial problem for this study that is development planning. It is useful in assisting planners from developed flow accumulation area. From this study, planners can identify flow accumulation area and floods occurrence developed area in Kuantan district can be avoided. Suggestion listed give further purification guide in upgrade development planning in Kuantan district. This will indirectly help involved parties carrying out works planning development with more easily and effectively.